O contrato de gestão e sua viabilidade como alternativa de gerenciamento na saúde pública - Silva, Dianna Mendes da (2013)
One of the major problems faced by the public health is its administration. Deploying SUS - National Health System and the Federal Constitution of 1988 and soon after with Law 8,080 of September 19, 1990, was a great achievement for the Brazilian population, however is considered to this day as a major challenge for the public manager. This work aims to present the management contract as an alternative to the problems faced in the management of public health. This is an issue that involves the public administration at all levels, from the federal to the city, but it is much more problematic at the municipal level. The main function of the management contract is setting targets to be achieved by the Social Organization, Third Sector organization, along with the government, for them to build an effective and sustained public policy. The methodology used was the literature research. As a result of this proposed study mainly focused on the welfare end of the population, who are often the most affected by the lack in the provision of public services, on the other hand, this alternative also aims to provide an option for the management and operation manager, who must always have new tools for solutions to problems encountered on a daily Public Administration.